دور نظام الموازنة العامة في تحقيق الاستدامة المالية في الجزائر - دراسة قياسية لحالة الجزائر 2000-2020: The role of the general budget system in achieving financial sustainability - a record study of the case of Algeria 2000/2020 - جبارة مراد, (Journal of North African Economies, 2025)
This study aims to analyze and measure financial sustainability, through the role of the general budget system. For this purpose, we touched on the most important basic concepts as an introduction to the study, then analyzed the reality of the public budget during the study period, and the most important indicators of financial sustainability, then the standard study using one of the modern models through the integration test The commonality according to the ARDL methodology and the existence of a long-term relationship between expenditures as a dependent variable, regular revenues, petroleum taxation, and oil prices as explanatory variables. It means that the general budget during the study period is in financial sustainability, but the capacity of financing is linked to the price of oil and the challenges that the budget faces in light of the collapse of oil prices, which necessitates to expedite and activate the adopted reform policies.